Sexual behaviour and risk factors for the acquisition of human papillomavirus infections in young people in Italy: suggestions for future vaccination policies - Panatto Donatella; Amicizia Daniela; Trucchi Cecilia; Casabona Francesca; Lai Piero; Bonanni Paolo; Boccalini Sara; Bechini Angela; Tiscione Emilia; Zotti Carla; Coppola Rosa; Masia Giuseppina; et al. (BMC, 2012)
Abstract Background Human Papillomavirus (HPV) is the most common sexually transmitted infection. The main risk factors correlated with HPV infection are: early sexual debut, the number of partners, frequency and type of sexual contact and partner's sexual histories. We surveyed sexual habits among young people in order to provide information that might orient decision-makers in adopting HPV multi-cohort vaccination policies. Methods We administered a questionnaire to students (14-24 years old) in five Italian cities. Results 7298 questionnaires were analyzed (4962 females and 2336 males); 55.3% of females (95% CI 53.9-56.7) and 52.5% of males (95% CI 50.5-54.5) reported regular sexual activity. The mean age at sexual debut was 15.7 ± 1.6 and 15.6 ± 1.6 for females and males, respectively, and the median age was 16 for both sexes. With regard to contraceptive use during the last year, 63.6% of males and 62.8% of females responded affirmatively; 42.6% of males and 42.8% of females used condoms. Conclusion The results reveal precocious sexual activity among respondents, with the mean age at first intercourse declining as age decreases. Condom use proved to be scant. Considering lifestyle-related risk factors, males appear to have a higher probability of acquiring HPV infection than females. These data support the importance of promoting multi-cohort HPV vaccination strategies for females up to 25 years of age. It is essential to improve vaccination coverage through different broad-spectrum strategies, including campaigns to increase awareness of sexually transmitted diseases and their prevention.